Holonic and Multi-Agent Systems for Manufacturing Third International Conference on Industrial Applications of Holonic and Multi-Agent Systems, HoloMAS 2007, Regensburg, Germany, September 3-5, 2007, Proceedings - Marik, Vladimir; Vyatkin, Valeriy; Colombo, Armando Walter (Lecture Notes in Artificial Intelligence,, 2007)
The research of holonic and agent-based systems is developing rapidly, as is the community around this R&D topic. Despite the fact that real-life practical implementations of such systems remain surprisingly rare, the leaders in different branches of industry feel that the holonic and agent-based systems represent the only way to manage and control very complex, highly distributed systems in the future. The relevant R&D gains more and more support from both industry as well as academic sources. Quite naturally, the number of scientific events aimed at the subject field is also growing rapidly. We can see new lines of conferences like INDIN, while we can observe a strong focus of the already well-established conferences, like INCOM or ETFA, being shifted toward holonic and agent-based manufacturing systems. This is a good sign of the increasing recognition and importance of the field. We are convinced of the worth and importance of the continuation of the HoloMAS events, which have served as pioneering melting pots for ideas connected with distributed decision making and control in industry and which have already gained international reputation.